The Effect of a Patient Activation Tailored Intervention on Type 2 Diabetes Self-Management and Clinical Outcomes: A Study from Saudi Arabian Primary Care Settings - Nasser Almutairi; Vinod Gopaldasani; Hassan Hosseinzadeh (Journal of Diabetes Research)
Background. Type 2 diabetes mellitus (T2DM) is a global public health challenge. T2DM self-management, including diet, physical activity, blood glucose self-monitoring, foot care, and adherence to medication, is considered a primary tool for managing diabetes. Patient activation, an individual’s knowledge, skill, and confidence in managing their health and healthcare, was recognized to be associated with better T2DM self-management and clinical outcomes. Patient activation intervention has been described as a potential approach for enhancing chronic disease self-management. This study is aimed at examining the effect of a patient activation-tailored intervention on T2DM self-management and clinical outcomes in primary care settings in Saudi Arabia. Method. A pre- and postintervention study was conducted among ≥18 years old T2DM patients attending primary healthcare centers in Saudi Arabia. Collected data included demographics, clinical data, the Patient Activation Measure (PAM), the Summary of Diabetes Self-Care Activities (SDSCA), the diabetes knowledge test (DKT2), the problem area in diabetes test (PAID-5), and the diabetes quality of life test (DQOL). The intervention was tailored based on the participants’ patient activation level. The intervention consisted of monthly face-to-face sessions for three months and a telephone follow-up per month for three months postintervention. Descriptive statistics, a paired sample t-test for scale variables, and Wilcoxon’s signed-rank test for categorical variables were used for data analysis. Results. A total of 82 patients, mostly female (61%) with a mean age of 51.3±9.9 years old, completed baseline and postintervention surveys. After six months of intervention, there was a significant change in patient activation score from 54.74 to 61.58 (p<0.001), hemoglobin A1c (HbA1c) from 8.38 to 7.55 (p<0.001), and body mass index (BMI) from 30.90 to 29.16 (p<0.001). Also, there was a significant change in SDSCA scores (diet from 3.12 to 3.67, exercise from 2.54 to 3.49, and blood glucose self-testing from 2.37 to 3.24) (p<0.001) and DKT from 6.29 to 7.22 (p=0.01). Conclusion. Our findings suggested that tailoring interventions based on patients’ activation levels is more likely to yield promising T2DM self-management and clinical outcomes.